Pengaruh Pemberian Pasir dan Jerami Padi terhadap Beberapa Sifat Tanah dan Umbi Tanaman Porang - Narka, I Wayan; Arthagama, I Dewa Made; Sumarniasih, Made Sri (Agrotrop : Journal on Agriculture Science, 2024)
Research on the Effect of Sand and Rice Straw Application on Some Soil Properties and Porang Plant Tubers has been carried out. This research aimed to determine the effect of sand and rice straw application on some soil properties and porang plant tubers. The design used was a Factorial Randomized Block Design with 3 replications. The sand provision factor consists of 3 levels: P0 = no sand, P1 = 10% sand, and P2 = 20% sand. The rice straw factor consists of 3 levels: J0 = no rice straw, J1 = 10 tons of rice straw /ha, and J2 = 20 tons of rice straw /ha. Several soil properties were observed: bulk density, soil organic C, levels of nitrogen (N), phosphorus (P), and potassium (K). The growth parameters of porang plants that were observed included plant height, number of tillers, plant dry weight, fresh weight of tubers, and oven dry weight of porang plant tubers. The results of the research showed that the interaction between the treatment of sand and rice straw on porang growth, tuber yield, and soil properties was not significant. A single treatment of rice straw had a significant effect on porang growth, porang tubers, bulk density, and C-organic soil. Application of 20 tons/ha of rice straw can increase oven-dry tuber weight by 119.51% compared to the control. The sand treatment did not show any significant effect, either on the porang plants or several soil properties.